Happy, happy Chinese New Year! - Demi. (New York : Crown Publishers, 2003)
Examines the customs, traditions, food, and lore associated with the celebration of Chinese New Year.
Book Links (A.L.A.)
Horn Book
Wilson's Children
5.1
5-8.
5-8
Keywords: Chinese New Year -- Juvenile literature; Chinese New Year; Chinese New Year; China -- Social life and customs -- Juvenile literature; China -- Social life and customs; China -- Social life and customs